تأثیر التطعیم بأیونات النیودیمیوم الفعالة Nd+3 على طیف الفلورة لزجاج التلیریت TeO2 - كاظم فراس جواد (Iraqi Journal of Physics, 2009)
In the present work, the fabrication techniques of type of Nd +3-glass laser active media : namely, Neodymium- Tellurite glass, where the glass system(TeO2(1-x) - BaOZnO- Nd2O3x) for values of (X=1,1.5,2,2.5,3,3.5 wt%) was used. Measurements have been taken for the signal of fluorescence spectrum of Nd+3- glass samples. The fluorescence spectrum, for one of the samples, has been taken, after the sequences of polishing for the out surface. The results give signal of fluorescence spectrum for the samples. Intensity of the peak of the signal increases with Nd +3 concentration. The fluorescence at (l=1.06 mm) for one of the samples has been detected and the fluorescence line width was (100 cm-1). The cross section of stimulated emission for this type of laser active media (sp(lp=1.06 mm)=3.59*10-20 cm2), and the results compared with the published data.